Dispersion of ammonia from a poultry farm in Santa Bárbara (Cundinamarca, Colombia) and its qualitative assessment - Ruíz, Katherine (2020)
An analysis of the dispersion of ammonia from a poultry farm was carried out in the village of Santa Bárbara, municipality of Tena (Cundinamarca, Colombia). Four uncontrolled chicken houses were used in which measurements of ammonia concentrations were made in the centre of the sheds and every 250 m following the orientations according to cardinal directions (north, south, east, west). Measurements were made during a productive cycle of 50 days, with three readings per day (08:00, 12:00, 18:00). A qualitative assessment of social perceptions was also made to people living within a 1 km radius of the poultry farm. It was found that ammonia emissions were related to the reproductive cycle and not to the hours of the day. Also, the concentration of ammonia was related to temperature, but not to wind speed. The maximum distance with relevant concentrations of ammonia was 361 m, which does not represent a threat to the surrounding population; however, the population perceives impacts to the quality of life associated with offensive odours coming from the farm.